Dampak Kelompok Wanita Tani Hijau Lestari Dalam Peningkatan Kesejahteraan Keluarga Anggota Kelompok Desa Jati Kesuma Kabupaten Deli Serdang - Audea, Devi; Bengkel (Pusat Riset dan Inovasi Nasional, 2025)
. This study aims to determine and analyze the impact of the Hijau Lestari women farmers group on improving the welfare of family members in the Jati Kesuma village group in Deli Serdang Regency. This study uses a qualitative research method with a descriptive approach. The data obtained in the field was then analyzed to draw conclusions from the research results. The conclusions obtained from the family welfare indicators according to BPS show that the Hijau Lestari women farmers group has no impact on health and nutrition, education, consumption levels and patterns, and poverty indicators. The Hijau Lestari women farmers group also did not contribute to an increase in other social indicators in terms of crime and access to information technology, but the Hijau Lestari women farmers group had a positive impact on tourism by fostering a strong sense of community and social cohesion. The factors that hinder the Hijau Lestari women farmers group from having an impact on improving family welfare are the lack of systematic administration and the lack of member activity. Apart from the Hijau Lestari women farmers group, other factors outside the Hijau Lestari women farmers group include crime in the form of theft, which still occurs frequently and hinders the group's development, lack of land in home gardens and demonstration plots, lack of utilization of modern technology, and the influence of seasonal weather.